Exploring game-based psychological empowerment and its motivational and wellbeing effects - Vahlo, Jukka; Holm, Suvi K.; Kaakinen, Johanna K.; Koponen, Aki (Elsevier BV, 2026)
This study empirically investigates how individuals experience psychological empowerment through gaming compared to their daily life interactions. Drawing on a survey of 2,594 participants from Finland and Denmark, we examine the prevalence, predictors, and implications of psychological empowerment in gaming. Our findings show that 29 percent of respondents from the nationally representative subsamples in both countries report experiencing greater psychological empowerment in gaming than in life in general. Further analysis using Partial Least Squares Structural Equation Modeling (PLS-SEM) reveals that gameplay preferences, positive affect, and playtime predict game-based psychological empowerment. Moreover, the meaningfulness component of game-based empowerment significantly influences gaming motivation - particularly immersion, achievement, relaxation, and challenge motives - as well as subjective vitality in daily life, suggesting potential transfer effects. Adapting Spreitzer's (1995) model of psychological empowerment, this study contextualizes these findings within gaming experiences. The results contribute to a deeper understanding of psychological empowerment in games and offer insights for game design, emphasizing the value of creating meaningful and empowering play experiences.